GAMBARAN KEJADIAN GINGIVITIS PADA ANAK BERKEBUTUHAN KHUSUS (STUDI KASUS PADA ANAK TUNAGRAHITA DI SLB C DI KOTA SEMARANG) - Antonius Raga Wida Dirgantara; Henry Setyawan Susanto; Lintang Dian Saraswati; Ari Udiyono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Gingivitis is an inflammation of the gingival tissues with redness, enlargement of gingival tissue, and bleeding because of dental plaque accumulation and calculus in supra-gingiva and sub-gingiva. Intellectual development disorder children can get gingivitis. The aim of this research is to describe prevalence of gingivitis in intellectual development disorder children. This research is observational analytic with cross sectional approach and take 123 children as the sample using total sampling. The index of gingiva is collected during the research. From 101 respondents, 73.3% children have gingivitis. The advice given to parents is to help their children during tooth brushing, to school and department of health are doing an education of preventing gingivitis and practice brushing teeth with correct technique.